Dream homes and dead ends in the city: a photo essay experiment. Issue 7 (20th April 2017) - Fast, Danya
Abstract: Research focused on the relationship between place and health demonstrates that it is complex and shifting, as overlapping social, historical, institutional and political and economic processes continually transform the landscapes in which lived experiences are embedded. Understanding this relationship requires knowledge of the situated meanings and local worlds that ethnographic methods are well suited to investigate. However, even conventional ethnographic methods can be inadequate to capture the embodied, lived experience of place – experiences in which the sensory and inner processes of memory and imagination are often privileged. Accessing these experiences and processes can require more experimental methodological approaches. In this article, I present work from a series of photo essays created between 2011 and 2016 by 15 young people who inhabit the social, spatial and economic margins of Vancouver, Canada, and discuss some of the challenges and opportunities presented by this methodology. Created over 5 years, and broadly focused on how they understood, experienced and navigated their 'place' in the city in the midst of poverty, addiction, violence and physical and mental health crises, the photo essays young people produced are embedded with personal biographies and trajectories, as well as shared experiences of geography, precarity and possibility in Vancouver.